Tudor Redeemed Antony Tudor - Percival, John (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Rambert and Ballet West at the Edinburgh Festival. When Tudor made his ballet to the Kindertotenlieder it was by a long way the first use of any Mahler music for ballet. PALABRAS CLAVE: Gustav Mahler, Antony Tudor, Ballet West, Rambert Dance Company, Edinburgh Festival, Lilac Garden, Offenbach in the Underground, Dark Elegies.
Dentro del apartado "Edinburgh Festival".